2015
DOI: 10.1021/acs.jpcc.5b02944
|View full text |Cite
|
Sign up to set email alerts
|

Electron Transport in Graphene-Based Nanosensors for Eu(III) Detection

Abstract: We performed quantum chemistry density functional theory calculations to provide insight and to calculate the response of nanographene (or molecular-graphene)-based sensors using Eu­(III) complexes as a cold surrogate of trivalent actinide ions. We found that the electronic structure of graphene can be affected by its interaction with europium ions as well as with water molecules. We found an increase in electron transfer through the graphene-based device when exposed to a liquid sample of europium nitrate, Eu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…All quantum chemistry calculations are performed using the GAUSSIAN-09 Program . Density functional theory , with the hybrid functional B3PW91 is used for all calculations; such a functional has been tested in several type of applications. , The LANL2DZ basis-set with effective core potentials is applied for the transition elements Mo and Ni while the 6-31G­(d,p) basis-set , is used for the remaining atoms. Geometry optimization is performed using the Berny method. , A self-consistent convergence threshold of 10 –6 is used for the density matrix and 10 –8 for the root-mean-square and maximum density matrix error.…”
Section: Methodsmentioning
confidence: 99%
“…All quantum chemistry calculations are performed using the GAUSSIAN-09 Program . Density functional theory , with the hybrid functional B3PW91 is used for all calculations; such a functional has been tested in several type of applications. , The LANL2DZ basis-set with effective core potentials is applied for the transition elements Mo and Ni while the 6-31G­(d,p) basis-set , is used for the remaining atoms. Geometry optimization is performed using the Berny method. , A self-consistent convergence threshold of 10 –6 is used for the density matrix and 10 –8 for the root-mean-square and maximum density matrix error.…”
Section: Methodsmentioning
confidence: 99%
“…In any I−V type of sensor, the shape of the I−V is what determines the nature of the agent to be sensed. However, on the question of how selective is graphene for the detection of Eu, we have reported 20 , showing different shapes of I−V curves; thus, we expect that any other moiety will most likely show different I−V behavior.…”
Section: Discussionmentioning
confidence: 93%
“…For aqueous systems, Kumar et al 20 reported a change in the electrical conductance of graphene ribbons when europium nitrate bonds to graphene. However, the change in the electrical conductance of graphene is practically negligible when the europium ion is coordinated by three nitrate ions and water molecules, yielding a more stable complex than the cases with only one or two nitrate counterions.…”
Section: Atomistic Calculations Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The data of the lifetime for Eu-pcCPG-O and Eu-pcCPG-C were tted using bi-exponential decay, 69 indicating the presence of two distinct emitting centres which are most likely to appear due to two different coordination environments around the Eu 3+ centre in the Eu-pcCPG. The Eu 3+ centre in Eu-pcCPG carries two terpyridine units (occupying six coordination sites) and the remaining two coordination sites could be occupied by the water or nitrate anions or both (one water and one nitrate anion), 70,71 which leads to the Eu 3+ centres in two different coordination environments. This would change the ligand eld strength around the Eu 3+ centre in Eu-pcCPG that eventually results in the biexponential decay.…”
Section: Synthesis Characterization and Photochromism In Coordination Polymer Gelsmentioning
confidence: 99%